Antecedents of continuance intention in online learning systems among vocational college students: The moderating effect of gender - Li, Xia; Wang, Xiuling; Wei, Chenming (Frontiers in Psychology, 2022)
Background: The primary objective of this study is to determine whether the Expectation Confirmation Model can be expanded by external variables including computer anxiety, social interaction, and self-efficacy, to better understand the intention to continue using online learning systems in the post-pandemic era in vocational colleges. Moreover, this research argues that the intention to continuance using online learning systems of students may be gender-sensitive. Methods: The researchers surveyed 482 students from eight vocational colleges in Jiangxi Province using a structured questionnaire. Partial Least Squares Structural Equation Modeling is used to verify the research model. Results: The outcomes demonstrate that the proposed model adequately explains continuous use intention for online learning systems at the 76.6%confidence level. All of the newly introduced variables into the ECM are shown to be significant relevant to explicate continuous use intention. Our survey results show that gender differences in intention to continue using online learning systems exist objectively, but this difference is not a natural difference. Conclusions: This research makes up for gaps in the existing literature on online learning and discuss how learning may be made more long-lasting in intricate environments.